Pemanfaatan Lahan Kosonng dalam Budidaya Sayuran di Halaham Rumah - Dining Aidil Candri; Ida Wayan Brahmanda Menu Wedham (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Verticulture is a method of farming using planting media arranged vertically or stratified to take advantage of the limited space. Jagaraga Village is one of the villages located in Kediri District. A village with all its potential. One of them is the abundant water supply and the people who have enough land or large yards. However, it is unfortunate that the potential possessed by the community is not optimally utilized. Therefore, the purpose of this Community Service Program is to optimize the potential of the community and to facilitate the community in obtaining vegetables by cultivating vegetables using the verticulture method.